Infectious Complications in Injection Drug Use - Ryan Knodle; Lindsay Demers; Rachel Simmons (Association of American Medical Colleges, 2021)
Introduction The prevalence of opioid use disorder has increased steadily over the last decade (from 2.2 million in 2010 to 10.2 million in 2018) and with it, a surge in infectious complications associated with injection drug use (IDU). Trainees in internal medicine routinely diagnose, manage, and treat patients experiencing these infections in the hospital setting as well as screen for and immunize against other comorbid infections in the ambulatory setting. Methods This 90-minute, case-based, interactive workshop was led by two facilitators, an infectious diseases specialist and a senior internal medicine resident. To evaluate its effectiveness, we used a pre- and postsession survey administered at the beginning and end of the workshop. Learners were asked to rate comfort level in recognizing, managing, and counseling about various IDU-related infections, as well as to answer specific, content-level questions. Result Thirty of 42 participants who attended the workshop completed the evaluation. There was a statistically significant change in participants' comfort level with diagnosing and managing IDU-associated infections as well as ambulatory standards of care for people who inject drugs (PWID) from pre- to postworkshop. Discussion Our workshop focused on the management and prevention of infections among PWID in both the inpatient and ambulatory settings. Learners demonstrated increased comfort in managing these conditions.